Spatial Analysis of Maritime Disasters in the Philippines: Distribution Patterns and Identification of High-Risk Areas - Glenn D. Aguilar; Yasmin P. Tirol; Ryan M. Basina; Jamaica Alcedo (ISPRS International Journal of Geo-Information)
Maritime accidents frequently occur in the Philippine archipelagic waters, often resulting in significant loss of life. These incidents highlight the urgent need for improvements in the country’s maritime safety systems. By utilising accident data from the Philippine Coast Guard and the GISIS IMO databases, spatial analytical approaches were employed to determine incident distribution patterns and resulted in an overall depiction of the likelihood component of risk across the country’s territorial waters. Kernel density and hotspot analysis revealed areas where incidents were concentrated and where statistically significant hotspots occurred. The Maxent tool was used to develop risk likelihood models for the incident locations using environmental rasters representing wind speed, significant wave height, depth, surface current, land distance and port distance. Model performance metrics including the AUC, TSS and Kappa were used to compare the two datasets and provide confidence on model robustness. Variable contribution figures showed that land distance is the most influential variable, with the majority of high-risk areas predominantly located near population centres. The resulting maps provide an intuitive and informative depiction of the characteristic patterns of maritime accidents in the country, identify areas of high risk requiring immediate attention and offer valuable insights to support strategies for improving and enhancing the country’s maritime safety.